Closure Investigation on Cloud Condensation Nuclei Ability of Processed Anthropogenic Aerosols. Issue 15 (2nd August 2020) - Hu, Dawei; Liu, Dantong; Zhao, Delong; Yu, Chenjie; Liu, Quan; Tian, Ping; Bi, Kai; Ding, Shuo; Hu, Kang; Wang, Fei; Wu, Yangzhou; Wu, Yunfei; et al.
Abstract: Whether the cloud condensation nuclei (CCN) ability of aerosol could be predicted by compositions has been long debated. Measurements of submicron aerosol compositions and size‐resolved CCN activation fraction were conducted at a mountain site (1, 344 m) near Beijing region during wintertime. The site is influenced in the noon‐afternoon by ground anthropogenic sources through convective mixing (CM) and for certain period received aged pollutants by regional advection (RA). By comparing the measured CCN‐derived hygroscopicity parameter ( κ CCNc ) with that predicted using chemical composition in bulk ( κ chem ), we found for CM period, κ chem overpredicted κ CCNc by 71 ± 11% (25 ± 13%) at SS = 0.1% (0.3%); whereas for RA‐only period, κ chem underpredicted by 13 ± 6% (18 ± 11%) at SS = 0.1% (0.3%). The former, representing fresher aerosols in smaller size, could be explained by not considering the size‐resolved composition, as the bulk measurement mainly reflects the features of larger particle. The latter is proved to result from the depression of droplet surface tension by potential surface‐active organics and the possible liquid‐liquid phase separation occurring at moderate RH, and a use of depressed surface tension (than pure water) of 0.063 ± 0.002 J m −2 would reach an agreement. We propose that a hybrid approach combining size‐resolved composition and reduced surface tension, for fresher and aged sources, respectively, should improve the estimation of aerosol CCN ability. Plain Language Summary: The ability of cloud condensation nuclei (CCN) of aerosol is important in determining the aerosol‐cloud interaction and this affects cloud formation hereby having environmental and radiative impacts. Previous studies have intensively used the conveniently measured compositions in bulk, and link this with the CCN ability by assuming the surface tension of droplet as water's. In this study, we examined this conversion from bulk composition to CCN ability by direct measurements of both at a mountain site, representing the environment of the top of boundary layer for cloud initialization. The results showed that to reduce the uncertainty of composition‐determined CCN ability, a reduced surface tension should be applied for aged aerosols; and the use of size‐resolved chemical composition will improve the CCN prediction for fresh aerosol. We hereby propose that this hybrid approach for the respective fresher and aged sources should improve the estimation of aerosol CCN ability. Key Points: Aerosol CCN ability measured at a mountain site more realistically represents the condition for initializing the cloud formation compared to ground measurement Size‐resolved chemical composition should improve the prediction of CCN ability for fresh aerosol Reduced surface tension will improve the prediction of CCN ability for aged aerosol